Ten Myths on Democracy and Communication - Bissio, Roberto Remo (Kasarinlan: Philippine Journal of Third World Studies, 2008)
This article debunks ten myths regarding democracy and the media, namely: 1) dictatorships are sworn enemies of news media; 2) public opinion is effectively manipulated by dictatorships using mass media; 3) alternative media have only marginal influence compared to the big press and electronic media; 4) as censorship disappears, the alternative media gain ground; 5) alternative media must stick to rudimentary methods in order to remain authentic; 6) political parties that wish to grow must posses their own news media; 7) in a democracy, audience and circulation rule the fate of a program or a publication; 8) in a democracy, the press is not subject to official control; 9) only democracies are interested in democratizng information; and 10) Even if willing, it is difficult to change the contents of news, for there are no alternative sources and programs.